Determinants of homicides in the state of Bahia, Brazil, in 2009 - Carlos Augusto Moreira de Sousa; Cosme Marcelo Furtado Passos da Silva; Edinilsa Ramos de Souza (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
PURPOSE: To carry out a study of association between socioeconomic and demographic factors and homicides in general population, in the state of Bahia, in 2009. METHODS: This is an ecological study. The data were collected from the database of the Information System about Mortality of the Ministry of Health, from the Brazilian Institute of Geography and Statistics and the Institute of Applied Economic Research. The Global Moran index was calculated for the detection of spatial autocorrelation, and the Local Moran index was calculated for the detection of spatial Clusters. The transformation in the variable answer (homicides rates) was performed and it was shaped using the Conditional Autoregressive Model. RESULTS: The data showed spatial autocorrelation. Two clusters of municipalities with high rates of homicides were identified, one located predominantly in the Greater Metropolitan Region of Salvador and the other in the South Region of Bahia, especially Eunápolis and Lauro de Freitas, which had the highest rates. The Average Residents Variables, local GDP and the Percentage of Illiteracy presented an inverse association with homicide rates, and the variables Firjan's municipal development index of work and income. Enrolment in high school and the Average of Bolsa Família were directly associated. CONCLUSIONS: The urbanization process, in most cases, not controlled by the State, in most cases, made the cities bigger and with better socioeconomic conditions, attraction centers for people with different socioeconomic levels, increasing the social inequality among the residents of these regions, with parallel increase in homicide rates.